Access and Disclosure of Personal Health Information: A Challenging Privacy Landscape in 2016-2018 - Kloss, Linda L.; Brodnik, Melanie S.; Rinehart-Thompson, Laurie A. (Yearbook of Medical Informatics, 2018)
Objectives: To assess the current health data access and disclosure environment for potential privacy-protecting mechanisms that enable legitimate use of personal health information while preserving the rights of individuals. To identify the gaps and challenges between increasing requests and expanding uses of such information and the regulations, technologies, and management practices that permit appropriate access and disclosure while guarding against harmful misuse of such information.Methods: A scoping literature review focused on (1) regulations affecting access and disclosure of personal health information, (2) the uses of health information that challenge access and disclosure boundaries, and (3) privacy management practices that may help mitigate gaps in protecting patient privacy.Results: Countries and jurisdictions are developing laws, regulations, and public policies to balance the privacy rights of individuals and the unprecedented opportunities to advance health and health care through expanded uses of health data. Regulations and guidance are evolving, but they are outpaced by the increasing demand for and the challenges of managing access and disclosure. Mechanisms such as consent and authorization may not always be adequate. Mechanisms that advance principled stewardship are more important than ever.Conclusions: Access and disclosure management are important dimensions of privacy management practices. This is a volatile period in which diverging public policies may reveal how best to balance access and disclosure of personal health information by individuals and by institutional custodians of the information. Approaches to access and disclosure management, including the roles of individuals, should be a focus for research and study in the years ahead.
Keywords: Privacy; health data access; disclosure; Health Information Portability and Accountability Act; General Data Protection Regulation; information governance